Late Paleozoic-Triassic evolution of the paleo-Loppa High, linked to tectonic events and depositional patterns - Bjørkesett, Siri Sagvåg (2009)
Seismic 2D datasets and well ties, linked up to previous studies done in the Loppa High area are the major elements of the thesis work. To better resolve the geological history of the paleo-Loppa High area the depositional patterns, structural elements, tectonic events have been studied using seismic facies interpretation and other tools in Kingdom software. Backstripping and structural restoration have also been carried out on a profile across the high. The main result is a geological evolution of the paleo-Loppa High starting in Carboniferous which was characterized by tectonic stable conditions. Sequences display a uniform thickness throughout the area. In late Carboniferous (Late Pennsylvanian?) the half-graben, situated at the base of the eastern flank, south on paleo-Loppa High was initiated. The upper Gipsdalen unit is thickening in the half-graben. Sediments were deposited throughout the area. In Early Permian (early Sakmarian?) movements in the half-graben continued, in addition to the initial movements on the main western boundary fault of the paleo-Loppa High. Evaporites and a carbonate platform are interpreted. Sediments were deposited throughout the area until the end of the Bjarmeland Group. In Kungurian times the first of two main tectonic events in the formation of the paleo-Loppa High structure occurred. The high was sub-aerially exposed and a barrier to sediments prograding from east to west. The Tempelfjorden Group onlapped paleo-Loppa High, while the western basin was in a state of sediment starvation. In late Permian (Guadalupian) the second main event occurred establishing the paleo-Loppa High structure. Faulting lead to tilting of the eastern flank, which exposed older sediments sub-aerially and erosional processes grinded the crest down to the nearly flat surface observed on seismic. Early-middle Triassic (Induan through early Ladinian) times were regionally a relatively calm period. This goes for the paleo-Loppa high area as well, except for three minor uplift events. Sediments deposited ...